The Prevalence of Negative Teacher-Related Factors in a Ghanaian Municipality’s Basic Schools - Osei, Ernest; Danso Mensah, Dominic Kwaku (Advances in Social Sciences Research Journal, 2018)
Our paper explored teacher- related factors responsible for low academic performance of junior high school pupils in the Effutu municipality of Ghana. We adopted the descriptive survey research design and educational productivity theory (theoretical framework) for this study. Questionnaires were used to gather data from three hundred participants. Using purposive sampling technique, the researchers selected 300 public basic school teachers as participants for the study. Using simple percentages and frequencies we established that several teacher- related factors contributed toward pupils’ low academic performance in the municipality. These include a lack of teacher job satisfaction leading to poor work habit, teachers failure to use teaching and learning materials, inability to complete the syllabi, a lack of opportunities for continuous professional development, poor preparation of lesson note, teacher lateness and absenteeism and less remedial teaching to improve pupils academic performance. We therefore recommend effective supervision of teachers’ instructional activities by circuit supervisors and head teachers. In addition, the Ghana Education Service should ensure adequate provision of teaching and learning materials and a possible review of teacher remuneration, incentives and allowances for improved teacher job satisfaction. More so, there should be regular organization of in –service training for teachers to sensitize them on various opportunities available for continuous professional development in order to improve their knowledge and skills based and its likely increase in educational outcomes.